TRANSFORMASI KESEHATAN MENTAL MELALUI LAYANAN PASTORAL KONSELING DI DESA MOPOLO, KECAMATAN RANOYAPO, KABUPATEN MINAHASA SELATAN - Tadung, Frieska Putrima; Matsino, Remalia Putri (HOSPITALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Community Engagement were carried out in Mopolo Village, Ranoyapo District, South Minahasa Regency. Some of the main problems in Mopolo Village are accessibility to the nearest health facilities, making it difficult to reach the existence of these facilities. This means that the people of Mopolo village do not receive enough health services. Apart from the problem of access to health facilities, the people of Mopolo village do not understand how important pastoral counseling services are to help them with aspects of spirituality. As a result of this community service activity, pastoral counseling was carried out accompanied by prayer and free health services provided by health workers from the Kawanua Nederland Ecumenical Church.